The rod synapse in aging wildtype and Dscaml1 mutant mice. - Mellisa R Clemons; Ren H Dimico; Cailyn Black; Megan K Schlussler; Michael J Camerino; Kirah Aldinger-Gibson; Amaris Bartle; Nathan Reynolds; Dylan Eisenbrandt; Aspen Rogers; John Andrianu; Bradley Bruce; et al. (PLoS ONE, 2023)
The retina is an intricately organized neural tissue built on cone and rod pathways for color and night vision. Genetic mutations that disrupt the proper function of the rod circuit contribute to blinding diseases including retinitis pigmentosa and congenital stationary night blindness (CSNB). Down Syndrome cell adhesion molecule like 1 (Dscaml1) is expressed by rods, rod bipolar cells (RBCs), and sub-populations of amacrine cells, and has been linked to a middle age onset of CSNB in humans. However, how Dscaml1 contributes to this visual deficit remains unexplored. Here, we probed Dscaml1's role in the maintenance of the rod-to-RBC synapse using a loss of function mouse model. We used immunohistochemistry to investigate the anatomical formation and maintenance of the rod-to-RBC synapse in the young, adult, and aging retina. We generated 3D reconstructions, using serial electron micrographs, of rod spherules and RBCs to measure the number of invaginating neurites, RBC dendritic tip number, and RBC mitochondrial morphology. We find that while rod-to-RBC synapses form and are maintained, similar to wildtype, that there is an increase in the number of invaginating neurites in rod spherules, a reduction in RBC dendritic tips, and reduced mitochondrial volume and complexity in the Dscaml1 mutant retina compared to controls. We also observed precocious sprouting of RBC dendrites into the outer nuclear layer (ONL) of the Dscaml1 mutant retina compared to controls. These results contribute to our knowledge of Dscaml1's role in rod circuit development and maintenance and give additional insight into possible genetic therapy targets for blinding diseases and disorders like CSNB.